2020
DOI: 10.1080/22221751.2020.1736954
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chicken CAR homology as a cellular receptor for the emerging highly pathogenic fowl adenovirus 4 via unique binding mechanism

Abstract: Since 2015, the prevalence of severe hepatitis-hydropericardium syndrome, which is caused by the novel genotype fowl adenovirus serotype 4 (FAdV-4), has increased in China and led to considerable economic losses. The replication cycle of FAdV-4, especially the emerging highly pathogenic novel genotype FAdV-4, remains largely unknown. The adenovirus fibre interacts with the cellular receptor as the initial step in adenovirus (AdV) infection. In our previous studies, the complete genome sequence showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 42 publications
4
25
1
Order By: Relevance
“… 44 It was reported recently that fiber1 was the major fiber for FAdV‐C4 adsorption. 45 , 46 We obtained the same findings and further confirmed that fiber2 was non‐essential for growing FAdV‐4 in a cultured chicken cell line, 31 which implies that fiber1 may only be slightly modified, whereas fiber2 is free for radical reconstruction. Recently, chicken CAR homology was identified as a cellular receptor for FAdV‐4.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“… 44 It was reported recently that fiber1 was the major fiber for FAdV‐C4 adsorption. 45 , 46 We obtained the same findings and further confirmed that fiber2 was non‐essential for growing FAdV‐4 in a cultured chicken cell line, 31 which implies that fiber1 may only be slightly modified, whereas fiber2 is free for radical reconstruction. Recently, chicken CAR homology was identified as a cellular receptor for FAdV‐4.…”
Section: Discussionsupporting
confidence: 75%
“…44 It was reported recently that fiber1 was the major fiber for FAdV-C4 adsorption. 45,46 We obtained the same findings and further confirmed that fiber2 was non-essential for growing…”
Section: Discussionsupporting
confidence: 75%
“…However, little is known about the molecular basis for the infection and pathogenesis of FAdV-4. Recently, our group and other group both revealed that Fiber-1, but not Fiber-2, directly triggered the viral infection of FAdV-4 via its shaft and knob domains [ 11 , 12 ]. Zhang et al reported that Fiber-2, but not Fiber-1, was identified as one of the major virulent determiners for the highly pathogenic FAdV-4 endemic in China [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al recently reported that Fiber-2 and Hexon, but not Fiber-1, were the virulent determiners for the highly pathogenic FAdV-4 isolates in comparison with the nonpathogenic strain [ 10 ]. Our group and other group’s recent studies found that the Fiber-1, not Fiber-2, directly triggered the viral infection of FAdV-4 via its shaft and knob domains [ 11 , 12 ]. However, the molecular basis of the Fiber-2 in the pathogenesis of the highly pathogenic FAdV-4 need to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other serotypes, serotypes FAdV-1, FAdV-4, and FAdV-10 have two fiber genes ( fiber-1 and fiber-2 ) [ 13 ]. Recently, our group and Wang’s group found that Fiber-1, but not Fiber-2, directly triggered the viral infection of FAdV-4 via its shaft and knob domains [ 14 , 15 ]. However, Zhang et al reported that Fiber-2, but not Fiber-1, was identified as one of the major virulent determiners for the highly pathogenic FAdV-4 endemic in China [ 16 ].…”
Section: Introductionmentioning
confidence: 99%